Scientific and Practical Characteristics of the Content of the Concept of «Operational and Search Measures» - KRYVYI, Andrii (University Scientific Notes, 2020)
The initial analysis of the state of research in the presented field of scientific intelligence shows that the study of scientific and practical characteristics of the content of the concept of «operational and investigative measures» in the modernized criminal procedure legislation of Ukraine by scientists and practitioners is fragmented. Until now, as now in scientific research, there are scientifically sound views on the «necessity», «priority», «expediency», «social conditionality» of the definition and content of the term «operational and investigative measures». There are many attempts to do this both theoretically and legally. Unfortunately, we are forced to state that there is no single developed scientific practice on the unified concept of «operational and investigative measures», and even more so its legislative consolidation today, despite the fact that this legal institution (phenomenon) it functions successfully, with the help of it certain tasks of operative-search activity are effectively solved, moreover, none, with a few exceptions, scientific-practical publication in the field of operative-search activity, does not do without its mention. The study of scientific and practical developments on the concept of «operational and investigative measures» allowed to formulate a unified definition of its content.